The effect of social capital on innovation through the mediation of ambidexterity and knowledge sharing in cement industry - Safira Andriani; Yasmine Nasution (President University, 2022)
Indonesia's economy is in a precarious state, made worse by the presence of the corona virus disease 2019 (Covid-19) pandemic. As a result, it is critical for businesses to be able to adapt to changes in an uncertain business environment. One option for the business to endure is through innovation. Previous study has established that social capital, the ability of the work team to be ambidextrous and knowledge sharing play a critical role in the creation of innovation inside the organization. The purpose of this study is to examine the effect of social capital on innovation through the mediation of ambidexterity and knowledge sharing in work teams at PT Indocement Tunggal Prakarsa Tbk, one of the largest private cement companies in Indonesia. The company operates in an unstable environment due to the global crisis, politics, price competition, and excess cement production capacity in Indonesia since 2016. This research is quantitative research with purposive sampling method using Structural Equation Modeling (SEM) analysis with Partial Least Square (PLS) method to test the hypothesis. The study's findings demonstrate that social capital can influence the generation of innovation when it is mediated through ambidexterity and knowledge sharing. This research is expected to assist enterprises in the Indonesian cement sector in surviving by fostering innovation within each work team.